Physical activity and overweight/obesity in adult Mexican population: the Mexican National Health and Nutrition Survey 2006 Actividad física y sobrepeso/obesidad en población adulta mexicana: encuesta Nacional de Salud y Nutrición 2006 - Luz María Gómez; Bernardo Hernández-Prado; Ma del Carmen Morales; Teresa Shamah-Levy (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To determine the association between physical activity and overweight/obesity in Mexican adults. MATERIAL AND METHODS: Cross-sectional design. Adults 20 to 69 years of age were included in the Mexican National Health and Nutrition Survey 2006 (ENSANUT 2006). The dependent variable was overweight/obesity and the independent variable was recalled physical activity. Analysis was by logistic regression, adjusting for sex, age, residence area, region, socioeconomic status, indigenous ethnicity, smoking, schooling, work activity, alcohol consumption and sitting time. RESULTS: Data from 15 901 adults were analyzed. The prevalence of overweight/obesity had an inverse association with physical activity among men but not among women. CCONCLUSIONS: The practice of physical activity was negatively associated with the prevalence of overweight/obesity only in adult men. These results underscore the importance of promoting physical activity to prevent and control overweight/obesity. OBJETIVO: Determinar la asociación entre la actividad física y el sobrepeso/obesidad en adultos mexicanos. MATERIAL Y MÉTODOS: Diseño transversal. Se incluyeron 15901 adultos de entre 20 a 69 años de edad, de la Encuesta Nacional de Salud y Nutrición 2006 (ENSANUT 2006). La variable dependiente fue sobrepeso/obesidad y la variable independiente fue la práctica de actividad física. Se usaron modelos de regresión logística ajustando por sexo, edad, área de residencia, región, nivel socioeconómico, indigenismo, tabaquismo, escolaridad, actividad laboral, consumo de alcohol y tiempo sentado. RESULTADOS: Se estudió a 15 901 adultos. La prevalencia de sobrepeso/obesidad tuvo una asociación inversa con la práctica de actividad física en hombres pero no en mujeres. CONCLUSIONES: La práctica de actividad física se asoció negativamente con la prevalencia del sobrepeso/obesidad únicamente en adultos hombres. Estos resultados subrayan la importancia de promover la actividad física para la prevención y control del sobrepeso/obesidad.